Influence of aerobic training on cardiovascular and metabolic parameters in elderly hypertensive women - Nayara F. T. Braz; Michelle V Carneiro; Fernanda Oliveira-Ferreira; Arthur N Arrieiro; Fabiano T Amorim; Márcia M. O. Lima; Núbia C. P. Avelar; Ana C. R. Lacerda; Marco F. D. Peixoto (International Journal of Preventive Medicine, 2012)
Background: Treatment of hypertension includes pharmacological and nonpharmacological interventions. Among the nonpharmacological interventions emphasizes the practice of regular physical exercise. However, the effects of aerobic exercise training on cardiovascular and metabolic parameters in elderly hypertensive women are still controversial. Objectives: The purpose of this study was to assess the effects of a walking program on metabolic and cardiovascular parameters at rest and during the recovery period following maximal exercise by hypertensive elderly women. Methods: Twelve elderly women with hypertension started a 2-week walking program. Rest blood cholesterol and anthropometric data, as well as blood pressure and heart rate at rest and after progressive maximal exercise were measured before and after training. Results: There were significant differences between the pre- and posttraining periods in VO 2 max, systolic blood pressure, diastolic blood pressure, and mean blood pressure. There were no changes in serum cholesterol levels after the training. During the recovery period following the progressive test, the fall in heart rate and mean blood pressure after 10 minutes of recovery was significantly higher after training. Conclusion: The proposed walking program did not alter serum cholesterol, but it did reduce resting blood pressure, improve aerobic performance and accelerate the fall in heart rate and mean blood pressure during the postprogressive maximal aerobic exercise recovery period in elderly hypertensive women.